Tackling disinformation through public administration recommendations – the Czech experience - Svoboda, Tomáš (Central European Public Administration Review, 2024)
Purpose: The aim of this paper is to critically evaluate the practice of public administration, in which it influences the addressees of public administration not through classical forms of public administration (e.g. administrative decisions) but by issuing recommendations to third parties, who then carry out regulatory interventions. Design/Methodology/Approach: The paper employs qualitative research methodology and a case study approach, focusing on the analysis of the specific situation in the Czech legal environment (including existing case law), which it frames as a broader issue that can be replicated and thus requires a more general solution. Findings: The text critiques the conclusion drawn from the Czech administrative court case law, which holds that public administration recommendations, if not legally binding, are not subject to judicial review. This conclusion suggests, at first glance, that public administration recommendations are an activity that has no legal limits. However, this interpretation is challenged in particular from the perspective of the rule of law. Specifically, the regulatory model outlined above, where public administration (the state) achieves its objectives by influencing third parties, raises concerns. Practical Implications: It is inadvisable to view non-binding public administration activity as incapable of infringing upon or otherwise influencing the rights of the addressees of public administration. Political accountability in this area seems inadequate, particularly because of a potential lack of transparency. On the contrary, changes to legislation and greater sensitivity from administrative courts towards these non-traditional forms of public administration might be advisable. Originality/Value: The topic can be considered novel, given the limited attention it has received in the literature. This is especially true for national literature (in the case of the Czech background on which the text is primarily based). While it has been explored within EU law in the context of debates about the nature of EU soft law, the issue under study does not align well with soft law (understood as a type of normative legal act, albeit legally non-binding). Therefore, only partial reference can be made to EU law. The topic of the paper is thus more closely related to the general principles of public administration rather than EU law, making it a presumably original contribution
Keywords: administrative justice; javna uprava; mehka zakonodaja; nezavezujoč akt; non-binding act; pravna država; priporočilo; public administration; recommendation; rule of law; soft law; upravno sodstvo